MODEL KEPEMIMPINAN KEPALA DESA BERBASIS KAPASITAS ADAPTIF DALAM MENINGKATKAN KINERJA PELAYANAN PUBLIK DI ERA DIGITAL - Yunita Fourina Dewi; Susilawati Susilawati (Program Studi Ilmu Pemerintahan FISIP Universitas Galuh, 2026)
The disruption era demands digital transformation in village governance, yet it is often hindered by apparatus resistance due to manual work culture and low technological literacy. This study aims to explore an adaptive capacity-based village head leadership model to overcome public service issues in Cikande Village. A qualitative case study method was used through data collection from interviews, observations, and documentation of purposively selected informants, namely the village head, service management apparatus, and residents. The findings offer a novelty that grassroots digitalization requires a